Slowly Expanding Lesions: A New Target for Progressive Multiple Sclerosis Trials?. (26th April 2022) - Simmons, Sarah B.; Ontaneda, Daniel
Abstract : The etiology of progressive accumulation of neurologic disability in persons with multiple sclerosis (MS) remains poorly understood, and this paucity of knowledge has hindered the development of therapeutics for those with progressive MS. One hallmark of progressive MS pathology is the presence of chronic active lesions, which are identified histopathologically by a hypocellular, demyelinated core with an edge of activated microglia and macrophages. 1 Postmortem, they are found in higher numbers in progressive MS, 2, 3 which suggests that these lesions may contribute to ongoing axonal injury and disease progression and may have different genetic underpinnings in white and gray matter. 4 Chronic active lesions are thought to increase in size over time and may represent a mechanism for worsening in progressive MS.